K+8=6(k-11)

Simple and best practice solution for K+8=6(k-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K+8=6(k-11) equation:


Simplifying
K + 8 = 6(k + -11)

Reorder the terms:
8 + K = 6(k + -11)

Reorder the terms:
8 + K = 6(-11 + k)
8 + K = (-11 * 6 + k * 6)
8 + K = (-66 + 6k)

Solving
8 + K = -66 + 6k

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + K = -66 + -8 + 6k

Combine like terms: 8 + -8 = 0
0 + K = -66 + -8 + 6k
K = -66 + -8 + 6k

Combine like terms: -66 + -8 = -74
K = -74 + 6k

Simplifying
K = -74 + 6k

See similar equations:

| 14-2x=20-5x | | (10a+7)(3a-4)=0 | | 3y+15x=6 | | -8a+3a=15 | | 99=(w+2)(w) | | 6p-10q= | | f(-1)=16x-2x | | 5n-3=-188 | | 2b-3.4=-1.74 | | 121/8+f=194/5 | | c=50i^2+2000 | | f(0)=16x-2x | | 7(6-x)=-28 | | 6x^2-2x^2-2=-9x+1 | | 3.6=6.4-0.7X | | 8x-8=-136 | | 0=cos(4x) | | (fx)=4 | | 22.50=4g+3.54 | | f(x)=16x-2x | | 8+5(s+5t)= | | 0=4cos(4x) | | 2t+4+8u+2t= | | H(t)=-16t^2+64t+ho | | k^2+100=20k | | 6=2x+2.5y | | 6t+4u+1+9u= | | 273+286+n=943 | | 4x^2-4x+7=6 | | 6x^2+43x-15= | | 7+u+9t+5u= | | 2sinx+3cosx=4x |

Equations solver categories